APPLICATION OF PLAY THERAPY USING BUSY BOOKS TO REDUCE ANXIETY IN PRESCHOOL CHILDREN DUE TO HOSPITALIZATION IN THE WEST ASTER WARD OF SARDJITO HOSPITAL - Aliefia Rahmawati; Sumarti Endah Purnamaningsih Maria Margaretha (Jurnal Kesehatan Karya Husada, 2026)
Background: Hospitalization in preschoolers causes anxiety in children, if left unchecked, can worsen the child's health condition. One of the therapies that can be done to reduce anxiety is to play therapy with a busy book. Objective: to find out an overview of the application of play therapy with busy book media in reducing anxiety in preschool-age children due to hospitalization in the West Aster Ward of Sardjito Hospital. Methods: Using a descriptive case study of one child who met the inclusion criteria. The intervention was carried out for three days with a total of three times of therapy, and anxiety level measurement using the Face Image Scale (FIS). Results: the application of play therapy with busy book media which was carried out for three days with a total of three therapies was obtained before and after therapy with an initial score of 5 (severe anxiety) with the child's facial expression showing the corners of the lips were very bent under the chin until crying, and after the therapy was carried out play therapy busy book To be a score of 2 (not anxious) with the child's waah expression showing the corner of the lips slightly raised upwards towards the eyes. Conclusion: Play therapy with Busy Book media has been shown to be effective in reducing anxiety levels in preschoolers aged 3-6 years due to hospitalization.